Criminal Policy Needed for the Recovery of Socio-Political Conditions for National Resilience Following the COVID-19 Pandemic - Eben Ezer Simanjuntak, Leonard; ., Budiyono (KnE Social Sciences, 2023)
The Large-Scale Social Restriction Policy (PSBB), later changed to the Enforcement of Community Activity Restrictions (PPKM), prohibits people from gathering. Restrictions on activities inside the community have impacted social life, including law enforcement. Criminal law enforcement must adhere to Law Number 8 of 1981 concerning the Criminal Procedure Code, which explicitly regulates the stages of criminal law enforcement in Indonesia. All these stages share something in common - a form of face-to-face examination of all subjects of criminal procedural law. Thus, there exists a problem in extraordinary circumstances. This study aims to identify criminal law enforcement policies during the COVID-19 pandemic in Indonesia to realize the Restoration of the Socio-Political Condition of National Resilience after the COVID-19 Pandemic. This research used a qualitative descriptive approach. The results of this study indicated that Law Number 8 of 1981 concerning Criminal Procedure Law as the basis for criminal proceedings (lex generalis) only conducts face-to-face examinations in criminal proceedings. Since COVID-19, there has been no regulation regarding online examinations, thus creating a legal vacuum (rechtsvakum) that needs to be filled. Discretion or criminal policy is needed to overcome problems, so the Attorney General’s Office, the Supreme Court, and the Ministry of Law and Human Rights on April 13, 2020, Award of Cooperation Agreement (PKS) for the Implementation of Trials Through Teleconferencing during the COVID-19 pandemic. Keywords: Criminal Policy, National Resilience, COVID-19 pandemic